2020
DOI: 10.3390/cancers12030708
|View full text |Cite
|
Sign up to set email alerts
|

The Microrna-143/145 Cluster in Tumors: A Matter of Where and When

Abstract: The establishment and spreading of cancer involve the acquirement of many biological functions including resistance to apoptosis, enhanced proliferation and the ability to invade the surrounding tissue, extravasate from the primary site, survive in circulating blood, and finally extravasate and colonize distant organs giving origin to metastatic lesions, the major cause of cancer deaths. Dramatic changes in the expression of protein coding genes due to altered transcription factors activity or to epigenetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…MiR-143/miR-145 are well-known tumour suppressor miRNAs dysregulated in several cancer types, including CRC. 53 Consistently, low levels of miR-143-3p have been observed in stool of patients with CRC 11 12 and their upregulation in stool of VT/VN supports the lower cancer risk observed in relation to these dietary habits. 54 55 These two miRNAs target some fundamental tight junction proteins.…”
Section: Discussionmentioning
confidence: 56%
“…MiR-143/miR-145 are well-known tumour suppressor miRNAs dysregulated in several cancer types, including CRC. 53 Consistently, low levels of miR-143-3p have been observed in stool of patients with CRC 11 12 and their upregulation in stool of VT/VN supports the lower cancer risk observed in relation to these dietary habits. 54 55 These two miRNAs target some fundamental tight junction proteins.…”
Section: Discussionmentioning
confidence: 56%
“…The available data point out the capacity of HPV for triggering metastasis and inducing more aggressive phenotypes in breast carcinoma (31). Furthermore, the evidence demonstrated that miR-143/145 expression was negatively related to lymph node metastasis, and patients with lower levels of miR-143/145 expression may be subject to poor prognosis malignancies (52,53). Collectively, our findings may present a novel mechanism by which HPV provokes breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, miR-143 is a comprehensively reported tumor suppressor miRNA and has been reported to directly bind and inhibit the translation of several oncogenes (reviewed in [ 29 , 30 , 31 ]). Therefore, downregulation of miR-143 has been described in a considerable number of cancer cell lines and tumors [ 31 ], including bladder cancer [ 32 , 33 , 34 ], and miR-143 usually exhibits an expression pattern similar to that of its evolutionarily conserved microRNA cluster partner miR-145 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%